The relationship between knowledge, culture, and the role of health workers and the behavior of women of reproductive age in the selection of contraceptive methods - Putri Wirasimpati; Agus Santi br Ginting; Ernita Prima Noviyani (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Contraception is the regulation of pregnancy through the use of devices or methods aimed at preventing pregnancy. The purposes of contraceptive use include delaying pregnancy, spacing pregnancies, and terminating fertility. There are various types of contraceptive methods, each with its own advantages and disadvantages (Susanti & Sari, 2020). One of the efforts implemented in the Family Planning (FP) program is the use of contraceptive methods. Purpose: To determine the relationship between knowledge, culture, and the role of health workers and the behavior of women of reproductive age in selecting contraceptive methods. Method: This study used a quantitative analytical survey with a cross-sectional design. The population consisted of all women of reproductive age who were active family planning participants at Cipayung Public Health Center, totaling 62 respondents. Data were collected using structured questionnaires and analyzed through univariate and bivariate analyses. The Chi-Square test was used to assess relationships between variables, with a significance level of 0.05. Results: The results showed that knowledge was not significantly associated with contraceptive method selection (p = 0.097), cultural factors were not significantly associated with contraceptive method selection (p = 0.397), and the role of health workers was also not significantly associated with contraceptive method selection (p = 0.706). Conclusion: There was no significant relationship between knowledge, culture, and the role of health workers and the behavior of women of reproductive age in selecting contraceptive methods.